MUSICAL & PEDAGOGICAL ACTIVITY OF DANICA KRSTIĆ IN SERBIA FROM 1903 TO 1940 (Heritage, 2022)
The subject of this work is a music-pedagogical activity by Danica Krstić from 1903 to 1940. The academic publications state a year of 1905/06 as a beginning of her pedagogical contributions.  In addition, the work provides a multitude of a concrete data on her music and pedagogical activities. By exploring a development of piano musicians education in Serbia, in the first half of the twentieth century, we establish that the work and contributions of Danica Krstić were insufficiently researched. Her contribution to the affirmation of young pianists and future piano pedagogical experts, and the improvement of concert related activity, are proven by this work numerous facts. She received many awards and testimonials for her efforts to advance Belgrade's music life in the first half of the 20th century. This research goal is to emphasize facts which place Danica Krstić a key piano pedagogical and playing artist, who to a large extent lead to systematised piano teaching and a work well organized within music educational institutions. By analysing the period of Danica Krstić music and pedagogical activity we conclude it has been intense and fruitful. We point out previously insufficiently explored professional activities of this influential piano pedagogical contributor, and believe in opportunity for a further research and analysis. We suggest exploring the plan and program for the piano teaching during that period, the contents of exams and concert programs, methods used while working with pianists and piano pedagogical experts departments, and teaching the blind and sight impaired students.
Keywords: Danica Krstić, teaching, piano, piano pedagogy